The Effect of Technical Competence (Hard Skill), Experience, and Non-Technical Skills (Soft Skill) on the Ability of the Auditors of the Financial Audit Agency of the Republic of Indonesia in Providing Expert Description at Trials - Muhammad Sahlan (Budapest International Research and Critics University, 2022)
An expert testimony provided by the forensic auditor as an expert will affect the Juror's confidence in deciding a case. For this reason, the testimony is needed that can give confidence to the Juror's and can make clear of the case being trial. This study aims to assess the extent to which Technical Competence (Hard Skills), Auditor’s Experience, and Non-Technical Skills (Soft Skills) affect the Auditor's Ability to Provide Expert Testimony in Court. This research is a descriptive quantitative study using primary data through a survey conducted to forensic auditor at the Audit Board of Indonesia. The results show that Technical Competence (Hard Skills), Auditor’s Experience, and Non-Technical Skills (Soft Skills) had a significant effect on the the Auditor's Ability to Provide Expert Testimony in Court.